Preliminary list pointed out of Formicidae of La Pampa province (Semiárida, 2020)
This work identifies some species of Formicidae (Hymenóptera) taken from the Santa Rosa City, Toay, Macachín, Padre Buodo, Lihué Calel and Casa de Piedra. There are some references for the myrmecological fauna of La Pampa and in some them the geographic distribution is enlarged.